Ódio coletivo: a perversão do rito - Rosa, Natália Rolim (2021)
Hatred exists and is one of the great dilemmas that the man of the 21st century must face. In the last decade, André Glucksmann's postulates in The Discourse of Hate (2004) have become prominent. Hatred emerges in a very robust, bulky and fierce body. What is this body? How is it structured? Why now? Hatred is a phenomenon of collective violence that is structured by persecutory mechanics in a context of social crisis. This hypothesis was both proven and disproved. André Glucksmann, René Girard, Byung-Chul Han, Sigmund Freud, Frans de Waal, Roger Dadoun, Umberto Eco, Hannah Arendt, Theodor Adorno are some of the authors used in the reflective exercise to understand their ambiguity. Rooted in deep social structures, in the genealogy of the human species and desire, hatred triggers the scapegoat's ritual mechanism and perverts it. The centrality of the body is removed from the ritual scene and replaced with speech. It establishes another language that resonates in a viral way through digital communication, mobilizing collective identifications by the sign of violence. Phenomenon of positivity, it does not seek to restore an ingrained body, convert a nefarious violence – it only disseminates its destructive drive. Collective Hatred is René Girard's Cultural Eclipse, André Glucksmann's Nefarious State, Umberto Eco's Ur-Fascism